2017
DOI: 10.1182/blood-2017-01-764209
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 blockade with nivolumab in relapsed/refractory primary central nervous system and testicular lymphoma

Abstract: Key Points Genetic analysis reveals frequent 9p24.1/PD-L1/PD-L2 copy-number alterations and increased expression of the PD-1 ligands in PCNSL and PTL. PD-1 blockade with nivolumab demonstrated activity in patients with relapsed/refractory PCNSL and PTL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
239
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(248 citation statements)
references
References 23 publications
3
239
0
6
Order By: Relevance
“…9,11,12 Recently, a study 13 found that all 5 patients with relapsed or refractory primary central nervous system large B-cell lymphoma or testicular large B-cell lymphoma treated with PD-1 blockade experienced an objective response, and 60% remained progression free at 13 to 17 months. Taken together, in certain lymphomas, chromosome 9p24.1 alterations, which include PDL1, are relatively common and are associated with high susceptibility to PD-1 blockade.…”
mentioning
confidence: 99%
“…9,11,12 Recently, a study 13 found that all 5 patients with relapsed or refractory primary central nervous system large B-cell lymphoma or testicular large B-cell lymphoma treated with PD-1 blockade experienced an objective response, and 60% remained progression free at 13 to 17 months. Taken together, in certain lymphomas, chromosome 9p24.1 alterations, which include PDL1, are relatively common and are associated with high susceptibility to PD-1 blockade.…”
mentioning
confidence: 99%
“…In patients with relapsed or refractory PMBCL including patients who were treated after autoHCT failure, Pembrolizumab was associated with a promising ORR that was durable for several months, although the study is still ongoing (50). Similarly, in smaller case series, anti-PD-1 inhibitors have demonstrated high efficacy in patients with Richter’s transformation of chronic lymphocytic leukemia (CLL) (51), relapsed NK/T cell lymphomas (52), relapsed/refractory primary CNS lymphoma (PCNSL) (53), or mediastinal gray zone lymphoma(54)…”
Section: Checkpoint Inhibition and Autohct (Table 1)mentioning
confidence: 99%
“…Importantly, the disease tends to relapse at extranodal sites, frequently the CNS [51]. Recent genomic analyses have shown that PCNSL and PTL share molecular features: On the one hand, mutations in MYD88, CD79B and CARD11 (as in ABC lymphoma) are frequently found [52] and, on the other hand, copy number alterations of 9p24.1 with the associated increased expression of PD-L1 and PD-L2 have been described in a high proportion of patients, providing the rationale to treat patients with CIs within clinical trials [53][54][55]. Initially, there have been anecdotal responses, and recently [56], a series of 5 patients (4 PCNSL, 1 PTL) has been reported.…”
Section: Primary Central Nervous System Lymphoma and Primary Testiculmentioning
confidence: 99%